Dampak Rasio Keuangan Dan Pertumbuhan Penjualan Terhadap Masalah Keuangan Pada Consumer Goods Industry - Ayu Safitri; Yuniatin Trisnawati D.K.W (Universitas Katolik Widya Karya Malang, 2024)
This study aims to explore the relationship between financial ratios, financial distress, and sales growth rates. The population used is made up of all consumer products industry sector companies that are registered on the Indonesia Stock Exchange between 2018 and 2020. Purposive sampling was used to select and collect 39 company samples in total. The investigation hypothesis was evaluated using logistic regression analysis. This study shows how financial ratios and sales growth both have a significant impact on financial distress. Meanwhile, show to some extent that leverage and profitability have a significant influence on financial hardship, but liquidity and sales growth do not.